The Impact of Intraspecies Variability on Growth Rate and Cellular Metabolic Activity of Bacteria Exposed to Rotating Magnetic Field - Marta Woroszyło (MDPI AG, 2021)
Majority of research on the influence of magnetic fields on microorganisms has been carried out with the use of different species or different groups of microorganisms, but not with the use of different strains belonging to one species. The purpose of the present study was to assess the effect of rotating magnetic fields (RMF) of 5 and 50 Hz on the growth and cellular metabolic activity of eight species of bacteria: Staphylococcus aureus, Pseudomonas aeruginosa, Proteus mirabilis, Klebsiella pneumoniae, Enterococcus faecalis, Enterobacter cloacae, Moraxella catarrhalis, and Bacillus cereus. However, contrary to the research conducted so far, each species was represented by at least four different strains. Moreover, an additional group of S. aureus belonging to a single clonal type but representing different biotypes was also included in the experiment. The results showed a varied influence of RMF on growth dynamics and cellular metabolic activity, diversified to the greatest extent in dependence on the bacterial strain exposed to the RMF and to a lesser extent in dependence on the frequency of the generated magnetic field. It was found that, with regard to the exposed strain of the same species, the effect exerted by the RMF may be positive (i.e., manifests as the increase in the growth rate or/and cellular metabolic activity) or negative (i.e., manifests as a reduction of both aforementioned features) or none. Even when one clonal type of S. aureus was used, the results of RMF exposure also varied (although the degree of differentiation was lower than for strains representing different clones). Therefore, the research has proven that, apart from the previously described factors related primarily to the physical parameters of the magnetic field, one of the key parameters affecting the final result of its influence is the bacterial intraspecies variability.